Climate change impacts on the conservation outlook of populations on the poleward periphery of species ranges: A case study of Canadian black‐tailed prairie dogs (Cynomys ludovicianus). (27th October 2017) - Stephens, Tara; Wilson, Sian C.; Cassidy, Ffion; Bender, Darren; Gummer, David; Smith, Des H. V.; Lloyd, Natasha; McPherson, Jana M.; Moehrenschlager, Axel
Abstract: Given climate change, species' climatically suitable habitats are increasingly expected to shift poleward. Some imperilled populations towards the poleward edge of their species' range might therefore conceivably benefit from climate change. Interactions between climate and population dynamics may be complex, however, with climate exerting effects both indirectly via influence over food availability and more directly, via effects on physiology and its implications for survival and reproduction. A thorough understanding of these interactions is critical for effective conservation management. We therefore examine the relationship between climate, survival and reproduction in Canadian black‐tailed prairie dogs, a threatened keystone species in an imperilled ecosystem at the northern edge of the species' range. Our analyses considered 8 years of annual mark–recapture data (2007–2014) in relation to growing degree days, precipitation, drought status and winter severity, as well as year, sex, age and body mass. Survival was strongly influenced by the interaction of drought and body mass class, and winter temperature severity. Female reproductive status was associated with the interaction of growing degree days and growing season precipitation, with spring precipitation and with winter temperature severity. Results related to body mass suggested that climatic variables exerted their effects via regulation of food availability with potential linked effects of food quality, immunological and behavioural implications, and predation risk. Predictions of future increases in drought conditions in North America's grassland ecosystems have raised concerns for the outlook of Canadian black‐tailed prairie dogs. Insights gained from the analyses, however, point to mitigating species management options targeted at decoupling the mechanisms by which climate exerts its negative influence. Our approach highlights the importance of understanding the interaction between climate and population dynamics in peripheral populations whose viability might ultimately determine their species' ability to track climatically suitable space. Abstract : Where species need to adapt to climate change via range shifts, populations at the range periphery are important. Struggling peripheral populations might benefit from climate change if currently hampered by harsh climatic conditions. Our 8‐year study of black‐tailed prairie dogs at their Canadian range edge suggests that survival and reproduction are indeed influenced by harsh winters, and also decline under drought‐like conditions. Expected increases in drought in the Northern Great Plains may therefore spell trouble for this species. Insights in our study on how climate exerts its negative effects, however, point to management options that might mitigate climate change impacts.